Design and Optimization of Fresnel Lens for High Concentration Photovoltaic System - Lei Jing; Hua Liu; Yao Wang; Wenbin Xu; Hongxin Zhang; Zhenwu Lu (International Journal of Photoenergy)
A practical optimization design is proposed, in which the solar direct light spectrum and multijunction cell response range are taken into account in combination, particularly for the Fresnel concentrators with a high concentration and a small aspect ratio. In addition, the change of refractive index due to temperature variation in outdoor operation conditions is also considered in the design stage. The calculation results show that this novel Fresnel lens achieves an enhancement of energy efficiency of about 10% compared with conventional Fresnel lens for a given solar spectrum, solar cell response, and corrected sunshine hours of different ambient temperature intervals.